Exploring the potential of a game-based preschool assessment of mathematical competencies - Chatzaki, Maria-Aikaterini; Skillen, Johanna; Ricken, Gabriele; Seitz-Stein, Katja (Frontiers in Education, 2024)
Background: Early mathematical competencies are foundational for later academical development. There is a need for valid and resource-saving approaches to assess those skills. The House of Numbers (HoN) is a newly developed linear board game that allows the assessment of preschool early mathematical competencies. This article aims to examine aspects of this 24-item screening such as its reliability and validity, and whether it can successfully identify children at risk of developing math difficulties. It also aims to explore children’s perceptions of the game-based HoN compared to a typical preschool math test. Method: A sample of 147 German preschoolers (Mage = 5 years 10 months, SDage = 5 months.) was evaluated with the HoN and with a standard instrument for assessing early mathematical competencies (MARKO-D). Additionally, a subsample of n = 47 children rated their perception of both tools. Results: The results speak against an effect of the game-setting on the children’s performance. Regarding the aspects of the reliability and the validity of the HoN, both tools were sensitive to age differences between five- and six-year-old children. The high correlation between the two assessments speaks for the convergent validity of the HoN. Furthermore, an item analysis based on the Rasch model showed excellent results for all items of the new game-based approach. The distribution of the items on the logit measurement ruler of the Person-Item map confirms, with only a few explainable exceptions, the developmental levels of the model the HoN is based on. A high person and item reliability confirm the internal consistency of the HoN. Regarding the diagnostic validity of the HoN, running a receiver operating characteristic curve resulted in a superior discrimination area under the curve. A sample relevant cut-off z-score was specified. Using this score as an indicator of low math performance resulted in high sensitivity, specificity and a high RIOC index. In addition, children’s explorative assessment of perception speaks in favor of the game-based assessment. Conclusion: All in all, the findings suggest, that the game-based measurement HoN can be a reliable, valid, time-saving, and attractive option for assessing early mathematical competencies in preschool settings.